Asian elephants and their status in Nepal: a review - Shrestha, Sami; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Wild Asian elephants (Elephas maximus) are one of the most endangered wildlife species in Nepal. Currently, there are approximately 200 to 250 wild elephants counted in Nepal. Of  them, 15-20 are in Jhapa district, 17 are in KoshiTappu Wildlife Reserve, eight in Sindhuli, and 45-50 in Parsa National Park andChitwan National Park. More  than 100 elephants are in Bardiya National Parks and adjoining municipalities, and 25-30 are in Suklaphanta National Park and adjoining municipalities.Elephant conservation is challenged by habitat fragmentation, obstruction of migratory routes and human-elephant conflict. The governments of Nepal, law enforcement, NGOs, and local communities have made various initiatives to conserve elephants. In the paper, we have outlined the current status of the elephant population, and its conservative efforts. This study may be a useful tool for the scientific communities and ecologists to protect elephants from extinction.